Gaps in studies of global health education: an empirical literature review - Yan Liu; Ying Zhang; Zhaolan Liu; JianLi Wang (Taylor & Francis Group, 2015)
Background: Global health has stimulated a lot of students and has attracted the interest of many faculties, thereby initiating the establishment of many academic programs on global health research and education. global health education reflects the increasing attention toward social accountability in medical education. Objective: This study aims to identify gaps in the studies on global health education. Design: A critical literature review of empirical studies was conducted using Boolean search techniques. Results: A total of 238 articles, including 16 reviews, were identified. There had been a boom in the numbers of studies on global health education since 2010. Four gaps were summarized. First, 94.6% of all studies on global health education were conducted in North American and European countries, of which 65.6% were carried out in the United States, followed by Canada (14.3%) and the United Kingdom (9.2%). Only seven studies (2.9%) were conducted in Asian countries, five (2.1%) in Oceania, and two (0.8%) in South American/Caribbean countries. A total of 154 studies (64.4%) were qualitative studies and 64 studies (26.8%) were quantitative studies. Second, elective courses and training or programs were the most frequently used approach for global health education. Third, there was a gap in the standardization of global health education. Finally, it was mainly targeted at medical students, residents, and doctors. It had not granted the demands for global health education of all students majoring in medicine-related studies. Conclusions: Global health education would be a potentially influential tool for achieving health equity, reducing health disparities, and also for future professional careers. It is the time to build and expand education in global health, especially among developing countries. Global health education should be integrated into primary medical education. Interdisciplinary approaches and interprofessional collaboration were recommended. Collaboration and support from developed countries in global health education should be advocated to narrow the gap and to create further mutual benefits.